(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2022)
Scope of the presented study was to evaluate the suitability and usefulness of ten different 3D-printed patient-specific organ phantoms designs, created with varying additive manufacturing methods. 17 physicians of the Pius-Hospital; Oldenburg and the Gesundheit Nord (GeNo); Bremen were interrogated for their assessment of different organ phantoms designs within the framework of a formative evaluation. The participants preferred dyed phantoms with a scale of 50% of the original.